2017
DOI: 10.1021/acs.jctc.6b01127
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prediction of Complex Structure and Affinity for a Flexible Protein Receptor and Its Inhibitor

Abstract: In order to predict the accurate binding configuration as well as the binding affinity for a flexible protein receptor and its inhibitor drug, enhanced sampling with multicanonical molecular dynamics (McMD) simulation and thermodynamic integration (TI) were combined as a general drug docking method. CDK2, cyclin-dependent kinase 2, is involved in the cell cycle regulation. Malfunctions in CDK2 can cause tumorigenesis, and thus it is a potential drug target. Here, we performed a long McMD simulation for docking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 48 publications
0
82
0
Order By: Relevance
“…Recently, dynamic docking to explore binding configurations between receptor proteins and their ligands by molecular dynamics (MD) simulations [ 1–5 ] has become possible by the use of GPGPU‐accelerated clusters [ 6 ] , which are clusters that make use of General Purpose Graphics Processing Units, and MD‐optimized supercomputers such as MDGRAPE. [ 7 ] Unlike traditional docking, dynamic docking enables accurate and extensive sampling of phase space by MD simulations, treating both ligand and protein receptor as flexible, while including solvation and entropic effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, dynamic docking to explore binding configurations between receptor proteins and their ligands by molecular dynamics (MD) simulations [ 1–5 ] has become possible by the use of GPGPU‐accelerated clusters [ 6 ] , which are clusters that make use of General Purpose Graphics Processing Units, and MD‐optimized supercomputers such as MDGRAPE. [ 7 ] Unlike traditional docking, dynamic docking enables accurate and extensive sampling of phase space by MD simulations, treating both ligand and protein receptor as flexible, while including solvation and entropic effects.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously applied McMD to the conformational sampling of proteins and peptides, [ 17,18 ] loop structure prediction of an antibody, [ 19 ] and for the docking simulations between receptors and their ligands. [ 1,2,4,5 ] Our recent McMD docking studies restrained the ligand inside a cylindrical region covering both the binding site and the bulk region, enabling us to successfully predict the native binding configuration in addition to generating a smooth binding/unbinding path. [ 2,4,5 ] However, to accurately predict the accurate ligand binding configuration without prior knowledge of the approximate location of the binding site by molecular docking still remains challenging, because a considerably more exhaustive search covering the entire receptor protein would be required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an MD study of several tens of proteins suggested that pocket conformations in the ligand‐bound state could not be fully produced by a ~100 ns simulation of the apo‐protein itself . To circumvent these limitations, several advanced MD methods that greatly enhance conformational sampling have been developed . Although these methods overcome both of the above‐mentioned problems, they have a high computational cost (e.g., MD simulations for a total of more than 10 μs, which cost several thousand CPU days, are required for evaluating a single protein‐compound pair).…”
Section: Introductionmentioning
confidence: 99%
“…[11] To circumvent these limitations, several advanced MD methods that greatly enhance conformational sampling have been developed. [12][13][14] Although these methods overcome both of the above-mentioned problems, they have a high computational cost (e.g., MD simulations for a total of more than 10 μs, which cost several thousand CPU days, are required for evaluating a single protein-compound pair).…”
Section: Introductionmentioning
confidence: 99%